The Influence of Exclusive Product Bundling and Live Streaming on Purchase Intention: The Mediating Role of Perceived Product Quality - Made Paramanandana Abhipraya; Hermeindito Hermeindito (Celebes Scholar pg, 2026)
This study examines how exclusive product bundling and live streaming influence purchase intention for Kahf skincare products on TikTok Shop Live, with perceived product quality as a mediating variable. Using a quantitative explanatory approach, data were collected from 162 respondents who had purchased Kahf products via TikTok Live within the past six months. Analysis using PLS-SEM (SmartPLS 4.0) shows that live streaming significantly enhances both perceived product quality and purchase intention through real-time interaction, host credibility, and visual demonstration. Exclusive product bundling increases purchase intention but reduces perceived product quality, suggesting that while bundles drive value-seeking behavior, they may weaken quality perceptions due to discount-oriented cues. Perceived product quality significantly boosts purchase intention and mediates the effects of both strategies, though negatively for bundling. These findings highlight how platform-native dynamics shape consumer evaluation and provide strategic insights for optimizing live-commerce marketing in the male grooming segment.